Strategi dalam Pengembangan Sekolah UPT SD Negeri 060806 - Agung Muhammad Nur; Lucky Tirta Nurarfiansyah; Dita Oktaviani; Ahmad Mukhlasin (CV Edujavare Publishing, 2023)
School development is a planned process to improve the quality of education and efficiency of educational institutions. By focusing on various aspects, such as curriculum, teaching methods, physical facilities, and staff development. School development is very important for the District/City Education Office in preparing education plans in their regions, with a focus on innovation and continuous evaluation. The aim of this research is to find out more about what is meant by strategic management in school development and what is involved in school development and remember that quality is very important in educational units. This study uses a qualitative method. The results of the research determine that strategies in school development are urgently needed to make it easier for educators and teaching staff to improve the quality of education.